A follow-up profile of women seeking pregnancy terminations in a clinic in urban Malaysia: 1998-2005 - Siti Fathilah Kamaluddin, (Penerbit UKM, 2010)
This is a follow-up study to assess the socio demographic profile of a sample of 28,605 women seeking pregnancy terminations at a private clinic in Penang over a seven year period as compared to an earlier study in 1995 of a sample of 23,986 women over a six and a half year period at the same clinic. This study was conducted using computerized patient medical records and paper reports generated from the computer data. The earlier 1995 study showed that the profile of a typical abortion client was a Chinese (60%), housewife (45%) in her late twenties (47%) with a monthly household income of less than RM1,200 (58%), having her first abortion (51%) and who had used contraception before (78%). For the seven year period from 1998-2005, the follow-up profile of a woman seeking an abortion in the same clinic in urban Malaysia was one with a monthly household income of less than RM2,000 (100%) in her late twenties (54%) who had used contraception in the past (85%). It is noted that the percentage of Malay respondents has increased (34%). The percentage of women who had a prior abortion at this clinic or elsewhere has also increased (68%), as compared to the preliminary study. Non-use of contraception remained an issue and traditional methods still outweighed the use of more effective contraceptive methods. In conclusion, fewer housewives and more Malay and Indonesian factory workers contributed to the clinic client profile over these seven years compared to that of the earlier study in 1995.